Music in the Middle Ages with an Introduction on the Music of Ancient times - Reese, Gustave 1899-1977 (London Dent, 1940)
The most authoritative study of medieval music in any language, Dr. Reese's book opens with a section devoted to what is known of music before the middle ages. It then deals with the background of Christian Chant and proceeds to treat separately -- among others -- the Syrian, Byzantine, Russian, Ambrosian, and Gregorian Chants. The history, notation, rhythm, modes, and forms of the last of these are discussed individually. Thereafter the author discusses secular monody in France, Germany, Italy, England, and Spain. The rest of the book is devoted to European polyphony from the 9th century to the death of Dunstable in 1453: the earlier stages of organum, the great music emanating from Notre Dame de Paris in the late 12th and early 13th centuries; French, Italian, Spanish, and German 14th-century polyphony, and polyphony in the British Isles, from the 12th to the middle of the 13th century. It reads as a continuing narrative but stresses consideration of musical style and includes a full bibliography and a list of phonograph records.
Keywords: Classical Antiquity (8th Century BC-6th Century AD); Middle Ages (500-1400); Music history